A Polyoxometalate Containing Circular P5W30 Units and Cubic Cu4 Clusters1. Issue 10 (20th November 2012) - Huang, Ling; Cheng, Lin; Wang, Sa‐Sa; Fang, Wei‐Hui; Yang, Guo‐Yu
Abstract: A polyoxometalate (POM) based on the assembly of [P5 W30 O110 ] 15– (P5 W30 ) units and copper ions, {(H5 P5 W30 O110 )2 [(en)4 Cu4 (μ3 ‐OH)3 (μ‐H2 O)]2 }[Cu(en)2 ]4 [Cu(H2 O)3 ]· 12H2 O (en = ethylenediamine) (1 ), has been made under hydrothermal conditions and characterized by single‐crystal X‐ray diffraction (XRD), elemental analysis, IR spectroscopy, thermogravimetric analysis, and power XRD; saturated P5 W30 was used as the precursor to make the new POM. POM1 is the first 3D P5 W30 ‐based POM linked by late transition metal copper complex ions, and it also features the rarely seen linkages of the saturated P5 W30 units and [Cu4 (μ3 ‐OH)3 (μ‐H2 O)] (Cu4 ) clusters. In the structure of1, the P5 W30 units and Cu4 clusters are alternately linked to form dimeric units and are further connected by two kinds of [Cu(en)2 ] 2+ complex bridges, which results in the 3D framework. Abstract : The reaction of P5 W30 and copper acetate results in a new 3D framework, in which the P5 W30 wheels join the Cu4 clusters to form dimeric units that are further linked by Cu complex bridges to produce an extended structure.